FISCAL POLICY PROBLEMS UNDER CONDITIONS OF FINANCIAL LIBERALIZATION - V. Urazayeva (Vestnik MGIMO-Universiteta)
The article under the title deals with the difficulties in pursuing national fiscal policy in conditions of international financial liberalization. The author analyzes the nature of liberalization of international capital flows and its positive and negative consequences for the economies of the countries which participate in global capital movement. The author especially highlights the fact that international financial liberalization often leads to economic crises and what is even more important to their rapid spread between countries due to their growing financial interdependence. The author distinguishes two groups of fiscal policy problems in conditions of international financial liberalization. The first group includes problems arising due to quick spread of the crises due to eliminating restrictions on crossborder capital flows. These are reduction in taxes and at the same time increase in budget spending, which often happens unexpectedly and substantially impedes fiscal policy. To illustrate these points the author refers to the statistics on Spain, the USA and the OECD as a whole. Moreover countries face another range of problems regardless of the business cycle phase. In the short term it is the necessity of large scale structural economic reforms to achieve the required level of financial liberalization, which often is a heavy burden on the state budget. In the long term the attention is paid to the problem of tax competition between countries, which affects the instruments of fiscal policy. The author notes that the negative consequences of global financial liberalization are relevant not only for recipient countries but for donor countries as well and emphasizes such a burning issue as "capital flight".